An investigation on the crack growth in aluminum alloy 7075-T6 under cyclic mechanical and thermal loads. (December 2022) - Kakavand, Erfan; Seifi, Rahman; Abolfathi, Mostafa
Highlights: Elevating temperature up to 190 °C in AA7075 increases the crack growth rate. Exponent m in Paris' law is almost invariant versus load frequency and temperature. For cyclic loads and temperatures, coefficient C inclines to a value for average temperature. Abstract: This study evaluates the consequences of mechanical load frequencies and thermal fluctuations on the fatigue crack growth in CT samples made by AA7075-T6. A controllable electrical resistance heating furnace/cooling fan setup was built for applying constant and variable thermal loads. In the first step, fatigue crack growth behavior was studied under different constant temperatures and a maximum load as 12 kN with R = 0. This evaluation indicated that the fatigue lives of the samples were reduced by increasing the constant temperature. Numerical simulations were performed by using the concept of the contour integral in evaluation of the stress intensity factors (SIFs) and crack growth based on Walker's Equation. Applying cyclic temperatures on the samples and altering the mechanical load frequencies revealed that reducing the load frequency from 30 to 10 Hz hasn't considerable effects on the fatigue crack propagation behavior. On the other hand, lowering the frequency to 5 Hz resulted in a minor decrease in the fatigue lives, while more reduction to 0.5 or 0.1 Hz, severely reduced the failure cycles.